The Impact of A Short Instructional Video in Improving Self-Efficacy in Eyedrops Application - Permata, Monica Adyah; Dharma, Andhika Guna; Puspasari, Denti (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2025)
Introduction: Eyedrops are primary treatment for many eye conditions, and patients often struggle with self-administration. In busy clinics, patients often receive little instruction on self-administration, and short instructional videos offer a practical solution. Study evaluated the impact of a short video on self-efficacy in eyedrop application. Methods: This quasi-experimental pretest-posttest study included 30 patients from a tertiary hospital eye clinic in Central Java (February and March 2025) that randomized to Direct Education Group (DEG), Video-Based Education Group (VEG), or Direct Education Assisted by Video Group (DEVG). Eyedrop techniques were video-recorded at pretest, post-test 1, and post-test 2; Self-efficacy as primary outcome was measured by number of correctly performed steps using 13-step checklist, then analyzed using multiple linear regression. Results: 80% reported eyedrop difficulties, 90% never received education, only 13.3% watched videos despite smartphone access. All groups improved self-efficacy significantly (p<0.001). DEG declined at post-test 2 (p=0.018), while DEVG maintained gains and showed superior scores vs DEG at 2-weeks (p=0.003) Conclusion: Short instructional videos significantly improve self-efficacy in eyedrop applications, with DEVG showing the most stable retention.